Investigação-ação e formação continuada de professores: deliberação curricular no contexto das escolas rurais (o exemplo de Iporã do Oeste/SC) - Wendling, Cléria Maria (2004)
The description and analysis of this dissertation result of a process of teachers’ education in context. The interactions narrated in this work were realized mainly with teachers of isolated schools from the municipal locality of Iporã do Oeste, Santa Catarina State, Brazil. Starting from realization of cycles based in the educational action-research, we seek to discuss collectively about the curriculum in a manner to construct more appropriate practices for the reality of the schools localized in the rural zone of Iporã do Oeste. The curricular actions developed are oriented starting from the construction of thematic nets designing a curricular deliberation process that fortifies the dialog, made possible collaboration between individuals and increases group autonomy from responsibility of all work by teachers, thus splitting with the gap between specialists and practioners, researchers and who are researched and between theory and practice.